Progress of Nanocomposite Membranes for Water Treatment - Ursino, Claudia; Castro-Muñoz, Roberto; Drioli, Enrico; Gzara, Lassaad; Albeirutty, Mohammad H; Figoli, Alberto (Membranes, 2018)
The use of membrane-based technologies has been applied for water treatment applications; however, the limitations of conventional polymeric membranes have led to the addition of inorganic fillers to enhance their performance. In recent years, nanocomposite membranes have greatly attracted the attention of scientists for water treatment applications such as wastewater treatment, water purification, removal of microorganisms, chemical compounds, heavy metals, etc. The incorporation of different nanofillers, such as carbon nanotubes, zinc oxide, graphene oxide, silver and copper nanoparticles, titanium dioxide, 2D materials, and some other novel nano-scale materials into polymeric membranes have provided great advances, e.g., enhancing on hydrophilicity, suppressing the accumulation of pollutants and foulants, enhancing rejection efficiencies and improving mechanical properties and thermal stabilities. Thereby, the aim of this work is to provide up-to-date information related to those novel nanocomposite membranes and their contribution for water treatment applications.
Keywords: silver (Ag); mixed matrix membranes (MMMs); nanocomposite; water treatment; carbon nanotubes (CNTs) zinc oxide (ZnO); titanium dioxide (TiO2); nanoparticles (NPs); graphene oxide (GO)